Pedro Antonio González Moreno, La erosión y sus formas (Antología 1986-2006), Madrid, Vitruvio, 2007, pp. 136. - Corredor-Matheos, José (Estudios Humanísticos. Filología, 2008)
Pedro Antonio González Moreno, La erosión y sus formas (Antología 1986-2006), Madrid, Vitruvio, 2007, pp. 136.